Inovasi Leksikal Bahasa Wotu - NFN Suparman (Badan Pengembangan dan Pembinaan Bahasa, 2019)
The purpose of this study is to describe the lexical innovation of Wotu dialect, namely describing a list of words that experience innovation by using qualitative methods or a direct approach to linguistic phenomena that occur in Wotu District, East Luwu District through an observation, interview, note taking technique and data reduction. The data obtained includes phonetic innovations consisting of substitution of vowel and consonant sounds, addition of vowel and consonant sounds, vowel sounds and consonants and consonant groups in the right position, meaning innovation, morphological innovations consisting of prefixes, suffixes, affixes and reduplications and lexical innovation consisting of lexical innovation, partial lexical innovation and full lexical innovation. ABSTRAKTujuan penelitian ini adalah untuk mendeskripsikan inovasi leksikal bahasa Wotu, yaitu mendeskripsikan daftar kata yang mengalami inovasi dengan menggunakan metode kualitatif atau pendekatan secara langsung terhadap fenomena kebahasaan yang terjadi di Kecamatan Wotu, Kabupaten Luwu Timur melalui proses observasi, wawancara, teknik catat, dan reduksi data. Data yang diperoleh mencakup inovasi fonetis yang terdiri atas penggantian bunyi vokal dan konsonan, penambahan bunyi vokal dan konsonan, penghilangan bunyi vokal dan konsonan serta gugus konsonan pada posisi kanan, inovasi makna, inovasi morfologi yang terdiri atas prefiks, sufiks, afiks dan reduplikasi, serta inovasi leksikal yang terdiri atas inovasi leksikal, inovasi leksikal parsial, dan inovasi leksikal penuh.